PROPOSTA DE ENSINO DE FÍSICA PARA EDUCAÇÃO DO CAMPO COM APOIO DE UNIDADES DE ENSINO POTENCIALMENTE SIGNIFICATIVAS (UEPS) - Luz, Franciele Cristiane de Oliveira Costa Alves da (2019)
Rural Education has been widely discussed in recent years, in view of the intention and the direction for improvement in the quality and access to knowledge by learners in rural areas. Physics, as a discipline that studies the phenomena of nature, is present in many of the activities developed in the rural areas. Thus, the present work sought to develop a proposal for the teaching of Physics with the support of PSTU (Potentially Significant Teaching Units) aiming to provide a meaningful learning within the Study of Movements, with the themes of Kinematics and Dynamics in Rural Education. The research was carried out with 1st year high school students, enrolled in a rural school in the municipality of Cascavel-PR, where they could develop potentially significant activities with the use of the physical concepts related to the themes, together with the experience of the student of the field. The research was carried out qualitatively and the results were obtained as action research. The main results showed an improvement in the teaching and learning of the topics addressed when related to activities experienced by the learners in the rural environment. Thus, the proposed use of PSTU for the teaching of Physics in Rural Education has brought positive results, such as a greater involvement of the students in the activities, an improvement in the understanding of the concepts of Kinematics and Dynamics, as well as the improvement in school performance of the students, observing these factors in the course of the activities and at the end of the school year, being therefore of great benefit for the development and advancement in the teaching of the discipline within the rural scope, since the importance of the scientific knowledge is within reach of all.